Heterogeneity of patient-reported outcome measures in clinical research - Terheyden, Jan H.; Gittel, Lisa; Jungblut, Julie; Taylor, Deanna J.; Holz, Frank G.; Crabb, David P.; Finger, Robert P. (Health and quality of life outcomes, 2024)
BackgroundThe use of patient-reported outcome measures (PROMs) in clinical research increases and use of heterogeneous instruments reflects how well diverse traits are captured by a medical specialty. In order to reflect the heterogeneity of current PROM use in ophthalmology, we reviewed the available literature.MethodsThe medical literature database Web of Science was searched for the most cited articles in clinical ophthalmology. Titles, abstracts and full text articles were reviewed for the use of PROMs and a list of the 100 most cited articles using PROMs was obtained and stratified by year of publication.ResultsA total of 1,996 articles were screened. Seventy-seven out of the 100 articles identified included one PROM, and the average number of instruments was 1.5 +/- 1.1. The most widely used PROMs were the National Eye Institute Visual Function Questionnaire (33%), the Ocular Surface Disease Index (14%) and the Medical Outcomes Study Short Form (13%). A simulation analysis suggested that the distribution of PROM use in ophthalmology study did not significantly differ from a power law distribution. Twenty-two percent and fifteen percent of articles did not reference and did not specify the PROM used, respectively. This rate decreased in the more recently published articles (p = 0.041).ConclusionsOur data suggest that the heterogeneity of PROMs applied in ophthalmology studies is low. The selection of PROMs for clinical studies should be done carefully, depending on the research goal.
Online veröffentlicht: 17. August 2024
Gesehen am 11.02.2025